OBSTETRIC AND PSYCHOLOGICAL CARE FOR PREGNANT WOMAN WITH HYPEREMESIS GRAVIDARUM WITH MODERATE ANXIETY - Hesti Yuniastutiningsih; Dini Latifatun Nafi'ati (Journal of Psychiatry Psychology and Behavioral Research, 2021)
Physical and psychological changes experienced by pregnant women, especially hormonal changes, cause symptoms of nausea and vomiting in early pregnancy. Excessive nausea and vomiting in early pregnancy and persist throughout pregnancy will cause physical and psychological complications. The existence of psychological problems in pregnant women can predispose to nausea and vomiting which then worsens. Emotional problems are also associated with the incidence of nausea and vomiting becoming more severe. Methods: the authors conducted extensive searches by scientific journals through trusted and frequently used databases, namely PubMed, Springer, and Science Direct. The keywords used were "hyperemesis" AND "psychological" with journal publication filters, the last 4 years, randomized clinical trials, systematic reviews, meta-analysis, human research subjects. Conclusion: care that focuses on mothers by applying the principles of holistic care, where patients not only receive midwifery care physically and biologically but include psychological, social, spiritual and cultural by involving their husbands in midwifery care is proven to accelerate the physical and psychological recovery of hyperemesis sufferers.